2019
DOI: 10.1111/jir.12609
|View full text |Cite
|
Sign up to set email alerts
|

‘We've made the best of it. But we do not have a normal life’: families' experiences of tuberous sclerosis complex and seizure management

Abstract: Background Tuberous sclerosis complex (TSC) is a complex multisystem genetic disorder. Approximately 84% of people with TSC have epilepsy. However, there is little literature available regarding families' experiences with TSC and seizure management. Therefore, the aim of the current study was to explore families' positive and negative experiences, and attitudes towards TSC, epilepsy and medical management of seizures. Methods Framework analysis informed an open exploration of families' experiences with TSC, ep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(25 citation statements)
references
References 26 publications
1
24
0
Order By: Relevance
“…Patients who have TSC with epilepsy have been found to have a significantly lower HRQL than those without epilepsy [ 45 ]. Burdensome after-effects of seizures included disrupted learning ability, fatigue, hemiplegia, and inability to communicate, eat, sleep, or relax for up to 24 h after an episode [ 46 ]. Patients reported frustration with their lack of independence due to their risk of seizures [ 46 ].…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Patients who have TSC with epilepsy have been found to have a significantly lower HRQL than those without epilepsy [ 45 ]. Burdensome after-effects of seizures included disrupted learning ability, fatigue, hemiplegia, and inability to communicate, eat, sleep, or relax for up to 24 h after an episode [ 46 ]. Patients reported frustration with their lack of independence due to their risk of seizures [ 46 ].…”
Section: Resultsmentioning
confidence: 99%
“…Burdensome after-effects of seizures included disrupted learning ability, fatigue, hemiplegia, and inability to communicate, eat, sleep, or relax for up to 24 h after an episode [ 46 ]. Patients reported frustration with their lack of independence due to their risk of seizures [ 46 ]. Another study has found that adult patients with TSC reported a loss of work productivity because of their condition [ 47 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations